GLOBAL SOLUTIONS FOR GLOBAL PROBLEMS - Gomero Gonzales, Nicko Alberto (2009)
Governments are implementing fiscal and monetary flexibility to reverse the negative effects of global crisis, but the results are sterile or minimal. Despite that injected billions of dollars to save their financial operations, multinational corporations continue to show signs of economic deterioration, so much so that flagship companies in the world have fallen into the worst crisis in the history. The fact that businesses continue in the pernicious cycle of crisis; although, financial aid is valid to assert that the paradigms of business also need a deep restructuring of their philosophy. That is why the crisis facing the model of globalization and economic merits of solutions that will not be sustainable over time, which requires global solutions, inclusive and integrate in such a way that leads to the world economy to grow symmetrically banishing all this action is know as speculators which was the factor that led to the global economy to one of the worst crisis of their history.